ETOS KERJA KEPALA SEKOLAH UNTUK PENINGKATAN KINERJA GURU SD MUHAMMADIYAH DESA HARJOWINANGUN KECAMATAN BELITANG KABUPATEN OKU TIMUR TAHUN PELAJARAN 2022/2023 - Puput Riani; Dhamroh Khair; Sri Lestari (UNISAN JURNAL, 2023)
This study aims to analyze the work ethics of the School Principal in improving the performance of teachers at Muhammadiyah Elementary School in Harjowinangun Village, Belitang District, East OKU Regency for the academic year 2022/2023. The research method used in this study is qualitative with data collection techniques through interviews, observations, and document studies. Participants in this study were the School Principal, teachers, and administrative staff at Muhammadiyah Elementary School in Harjowinangun Village. The results of the study indicate that the work ethics of the School Principal play an important role in improving the performance of teachers at Muhammadiyah Elementary School in Harjowinangun Village. The School Principal has a proactive attitude in finding solutions to problems faced by teachers and provides the necessary support to improve their performance. The School Principal also facilitates training and workshops for teachers and provides constructive feedback as an effort to improve the quality of learning in the school. Additionally, the School Principal provides motivation and clear guidance to teachers to improve their performance.